Jejak Kepemimpinan Ratu Kalinyamat (De Kranige Dame) - Inez Kalyana Azmi (Universitas Negeri Semarang, 2024)
This research seeks to analyze the local history of Ratu Kalinyamat Jepara, traces of Ratu Kalinyamat's leadership, and the impact of Ratu Kalinyamat's power on the people of Jepara. Furthermore, this article explains the problems of learning local history in schools, describes the life of Ratu Kalinyamat Jepara in detail and also provides an understanding of the leadership used by Ratu Kalinyamat when she was ruler of Jepara. Furthermore, this article also explains the political, economic and religious impacts of Ratu Kalinyamat's leadership on the people of Jepara in depth. The research method used is a historical research method which consists of 4 stages, namely heuristics, source criticism, interpretation and historiography. Based on research results, Ratu Kalinyamat used several leadership methods when ruling in Jepara, such as visionary leadership, patriotic leadership and open leadership. Then, Queen Kalinyamt was also called De Kranige Dame or which means a brave woman because she never gave up in expelling the Portuguese from Malacca. It didn't stop there, Ratu Kalinyamat was also highly respected by the Portuguese, earning her the nickname Rainha de Japora, Senhora Poderosa e rica, which can be translated as